Optimalisasi Pengetahuan dan Skill Perawat Tentang Perawatan Diabetes Melalui Program Pelatihan dan Pendampingan Penerapan SDKI, SLKI dan SIKI - Sulastri Sulastri; Harjati Harjati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder that will be suffered for a lifetime with the disease process continuing so that at one time it can cause complications. Comprehensive treatment must be carried out so that blood glucose levels in DM patients can be controlled and complications can be prevented as early as possible. Control of blood glucose in DM must be carried out through 5 pillars which include regulating diet, exercise, medication, monitoring blood glucose levels and education. The role of nurses in caring for DM patients includes the roles of care givers, counselors, educators, advocates who are oriented to the needs and health of patients. Nurses who act as educators and counselors in increasing the independence of patients and families to carry out integrated DM management. This role is carried out by carrying out nursing interventions regarding nursing management of DM patients. Efforts are needed to improve the competence of nurses in caring for DM patients. The solution to the problem is in the form of efforts to increase the knowledge and skills of nurses regarding the management of diabetes mellitus nursing care based on IDHS, SLKI and SIKI through training and mentoring and equipped with the distribution of DM care smart books for nurses. The target of this activity is nurses who work in Tugu Ibu hospitals in Cimanggis. The purpose of this activity is to improve the quality of care for DM patients. The output of this activity is an increase in the knowledge and skills of nurses in conducting assessments, determining diagnoses, planning, carrying out nursing actions and evaluating DM patients based on the SDKI, SLKI and SIKI which ultimately improves the quality of nursing care in DM patients. Keywords: Optimization, Treatment, DM, Training, Mentoring.